Vibrational Spectroscopic Characterization of Glycerol Reaction Pathways over Metal‐Modified Molybdenum Carbide Surfaces. Issue 1 (5th December 2019) - Wan, Weiming; Lin, Zhexi; Chen, Jingguang G.
Abstract: As the production of biodiesel increases, it is economically preferable to upgrade the excess by‐product, glycerol, into value‐added products. Metal‐modified molybdenum carbide (Mo2 C) is a class of promising catalysts for this application due to their promising hydrodeoxygenation (HDO) activity. In this work, Pt, Fe and Cu were used to modify the Mo2 C surface and tune the product selectivity of glycerol. Pt/Mo2 C showed reforming activity to produce syngas, Fe/Mo2 C cleaved all the C−O bonds of glycerol to produce propylene, while Cu/Mo2 C broke only one C−O bond of glycerol to form acetol. Consecutive temperature‐programmed desorption (TPD) experiments demonstrated an enhanced stability of all surfaces when compared to Mo2 C. High‐resolution electron energy loss spectroscopy (HREELS) characterization indicated that the Fe/Mo2 C surface weakened the C−O bonds of glycerol, while the Pt/Mo2 C surface showed no activity towards C−O bond cleavage. This study demonstrated that the Pt/Mo2 C, Fe/Mo2 C and Cu/Mo2 C surfaces were active, selective and stable for converting glycerol into syngas, propylene, and acetol, respectively. The combination of TPD and HREELS also served as an example of utilizing surface spectroscopy to identify the reaction pathways and intermediates on model catalyst surfaces. This should, in turn, provide insights to guide the design of metal‐modified carbide catalysts for the upgrading of biomass‐derived oxygenates. Abstract : Look closer : The combination of TPD and HREELS identified the various reaction pathways and intermediates of glycerol on metal modified Mo2 C surfaces. Glycerol was converted to acetol on Cu/Mo2 C, and to syngas on Pt/Mo2 C. Propylene was produced from glycerol on both Fe/Mo2 C and Mo2 C, and Fe/Mo2 C had better stability due to the modified surface oxophilicity.